English teachers’ knowledge on Higher Order Thinking Skills (HOTS) - Wisma Yunita; Syahrial Syahrial; Gita Mutiara Hati (English Review: Journal of English Education, 2020)
The Higher Order Thinking Skills (HOTS) has been embodied in the 2013 curriculum by the government of Indonesia, in which aims every individual in Indonesia has good skills at critical thinking, creative thinking, collaboration, and communication to face life in the 21st century. Therefore, the English teachers in Indonesia should have good knowledge of HOTS to teach their students. This study aims to investigate the knowledge of the Junior High School (JHS) and Senior High School English (SHS) English teachers on HOTS in Bengkulu province. Data obtained by providing a questionnaire containing questions with four answer choices (strongly agree, agree, disagree, and strongly disagree) in the form of Google form to 69 JHS English teachers and 74 SHS English teachers in Bengkulu province. The data were analyzed using simple statistics by calculating the average value of all answers from all question items and categorized them into Very Good (3.26-4.0), Good (2.6-3.25), Less Good (1.76-2.5), and Very Poor (1-1.75). The results of this study revealed that the level of knowledge of English teachers in Bengkulu Province on HOTS is in a good category (3.24) for JHS teachers and very good (3.31) for SHS teachers. These findings give contributions related to the knowledge of JHS and SHS English teachers in Bengkulu Province about HOTS.